Analisis Kemampuan Mahasiswa dalam Pemecahkan Masalah Matematis menurut Teori Polya - Netriwati, Netriwati (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This research aimed to describe students’ ability in solving mathematics problems according to Polya theory. According to writer’s experience in the subject of basic mathematics, the students had low ability in solving mathemathics problems. Therefore, the writer used the descriptive qualitative method to analyze problem-solving of mathematics according to Polya theory of semester two of IAIN students. Test and interview were used in collecting data. Based on analysis of simple statistic, it was found that students, whose high prior knowledge thought algorithmically in solving the question of problem-solving of mathematics, could understand the problems correctly and fluently. Students whose moderate prior knowledge thought algorithmically and not completely solved the questions of problem-solving. Furthermore, students whose low prior knowledge thought heuristic in solving the questions of problem-solving of mathematics.